Pediatric Endoscopy During COVID-19 Times - Shaoul, Ron; Day, Andrew S. (Frontiers in Pediatrics, 2021)
The global COVID-19 pandemic has led to healthcare resources being diverted or stretched, especially during periods of lock-down in affected countries. Disruptions to normal services have resulted in reduced or delayed provision of endoscopy in many countries, with consequent impacts on diagnosis or management of digestive diseases and upon endoscopy training. This review article aims to highlight key aspects of the impact of the pandemic upon endoscopy services, with a focus upon endoscopy in children.